Peran Orang Tua Pada Pembelajaran Jarak Jauh Ditinjau Dari Aspek Hasil Belajar - Fidela Michaela Vania; Ermawati Zulikhatin Nuroh (EJoES (Educational Journal of Elementary School), 2022)
With the emergence of the Covid-19 outbreak, the Ministry of Education, Culture, Research, and Technology issued Circular Letter number 15 of 2020 which contains about organizing learning from home during the emergency period of COVID-19's spread. That policy makes teaching and learning activities were carried out remotely. Researcher uses kualitatif deskriptif with data collection technique interview. The researcher uses triangulation to check the validity of the data which obtained from several sources. The result of the study shows that some parents are able to know enough about their role as parents in distance learning. It has been described in the indicators of student learning, students who get unsatisfactory learning outcomes can be indicated that the role of parents is low, it can be seen that the role of parents is important in achieving the success of student learning, especially during distance learning.